Metal-Free Oxidative C(sp3)–H Bond Couplings as Valuable Synthetic Tools for C–C Bond Formations - Rohlmann, Renate; García Mancheño, Olga (Synlett, 2013)
Metal-free oxidative methods for the direct functionalization of C(sp3)–H bonds to form new C–C bonds remain challenging. In this article, previous and recent results, the latter devoted to expanding the scope and synthetic applicability, on these metal-free oxidative C–C coupling reactions are highlighted.
Keywords: oxidation; C–H functionalization; metal-free; cross-coupling; alkenes